2008
DOI: 10.1016/j.ijid.2008.02.009
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of an independent lineage of dengue virus type 1 (DENV-1) and its co-circulation with predominant DENV-3 during the 2006 dengue fever outbreak in Delhi

Abstract: It is feared that the introduction of an independent lineage of the outbreak-associated strain of DENV-1 and its co-circulation with the deeply-rooted strain of DENV-3 in Delhi may result in yet another, possibly more severe outbreak in the near future.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
40
0
2

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 29 publications
2
40
0
2
Order By: Relevance
“…Subsequently, Central Western Indian states (Gujarat, Madhya Pradesh and Rajasthan) were affected [6,21]. By the end of 2006, sporadic cases of CHIKV infection along with massive dengue outbreak in Delhi were reported [22,34]. Few cases were also reported from Haryana and Uttar Pradesh [18,35].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, Central Western Indian states (Gujarat, Madhya Pradesh and Rajasthan) were affected [6,21]. By the end of 2006, sporadic cases of CHIKV infection along with massive dengue outbreak in Delhi were reported [22,34]. Few cases were also reported from Haryana and Uttar Pradesh [18,35].…”
Section: Discussionmentioning
confidence: 99%
“…Existe suficiente información que demuestra la coincidencia entre el cambio del serotipo predominante y el cambio en la incidencia del dengue, en áreas hiperendémicas de Latinoamérica y Asia (1,(5)(6)(7). También, se ha reportado incremento en la incidencia que coincide con la introducción de un genotipo distinto y con la diversificación genética del genotipo presente, la cual puede llevar a extinción, reemplazo y circulación simultánea de linajes (8)(9)(10)(11)(12).…”
unclassified
“…However, Singh and Seth 5 suggested that fragments of the capsid-premembrane junction region (CprM) might be a faster and cheaper alternative for sequencing short regions. Since then, CprM has been used by a number of authors [6][7][8] . Genes that code for non-structural proteins have also been sequenced and used in phylogeny studies 9 .…”
Section: Introductionmentioning
confidence: 99%